ANALISIS KETERSEDIAAN AIR DI SEBAGIAN WILAYAH DAS OYO HULU UNTUK KEBUTUHAN AIR DAERAH IRIGASI PAYAMAN, KECAMATAN SEMIN, KABUPATEN GUNUNGKIDUL - , ARUM RAHAYU ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Rain water sources from one of process in hydrology cycle, if it accumulated into overland flow will until main stream which add rate of blow. Rain and stream water which get main source for irrigation water avaibility. The purpose of this study is to determine availability, requirement and water balance for irrigation with abbreviated recommendation so that water availability can sufficient requirement. Water avaibility for Payaman Irrigation Region trades on rate of blowâs Oyo River at Semin Subdistrict. Where that rate of blow is determined from Neraca Air calculation of a part area of upper course Oyo Watershed with Thornthwaite- Mather Methode. It is used to irrigation water requirement, which covered water requirement for : (1) prepared land